Childhood Temperament Types Provide Specificity Over Dimensions in Predicting Early Adolescent Symptoms of Psychopathology: Genetic and Environmental Contributions - Alexys S. Murillo; Mary C. Davis; Leah D. Doane; Kathryn Lemery-Chalfant (Clinical Psychological Science, 2026)
Temperament is a heterogeneous construct that captures individual differences in reactivity and regulation. Traditionally, dimensions of temperament are used over temperament types that may better capture heterogeneity. Using a racially/ethnically and socioeconomically diverse sample of twins ( N = 997 twins; 51.4% female; 58.5% White, 24.0% Hispanic; 28.7% at or below the poverty line), we modeled associations between primary-caregiver-reported temperament (age: M = 8.43 years) and later cross-reporter factors of anxiety, depression, externalizing, and attention-deficit/hyperactivity-disorder symptoms (age: M = 10.88 years) and estimated latent genetic effects using temperament dimensions and types. The dimension of effortful control was negatively associated with all psychopathology symptoms over and above negative emotionality and surgency, and temperament types yielded more nuanced results. We also uncovered a larger role of the shared environment for temperament and symptoms of psychopathology independently and in their relation than previous research has suggested. Findings provide greater specificity to current understanding of the relation between temperament and psychopathology.